2009
DOI: 10.1128/jcm.01197-08
|View full text |Cite|
|
Sign up to set email alerts
|

High Levels of mecA DNA Detected by a Quantitative Real-Time PCR Assay Are Associated with Mortality in Patients with Methicillin-Resistant Staphylococcus aureus Bacteremia

Abstract: Persistent methicillin-resistant Staphylococcus aureus (MRSA) bacteremia is known to be a poor prognostic factor. While several PCR assays for the detection of MRSA in various clinical samples were recently reported, the possibility that a quantitative PCR assay could be used to quantify and monitor MRSA bacteremia has not been explored. In this study, we established a quantitative real-time PCR assay for the mecA gene using known copy numbers of a plasmid containing mecA DNA as a standard and the previously d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 48 publications
6
32
0
Order By: Relevance
“…Second, the local concentration of bacteria at an infectious site is much higher than in the blood. Recent patient studies using PCR have detected bacteria in amounts comparable with what we have used (38).…”
Section: Discussionmentioning
confidence: 86%
“…Second, the local concentration of bacteria at an infectious site is much higher than in the blood. Recent patient studies using PCR have detected bacteria in amounts comparable with what we have used (38).…”
Section: Discussionmentioning
confidence: 86%
“…In order to estimate the true concentration of pathogen DNA available in whole blood for molecular analysis from patients with bloodstream infections, we analyzed the data available in the literature. Organism-specific quantitative PCR has been used to measure the bacterial DNA present in whole-blood specimens from patients with sepsis, pneumonia, or suspected bloodstream infections (13,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Each of these studies analyzed whole-blood specimens from patients with suspected or confirmed infections rather than spiked samples for which the genome-to-viable cell ratio is expected to be close to 1:1.…”
Section: Repeated Analytical Testing By Pcr/esi-msmentioning
confidence: 99%
“…Advances in molecular techniques have led to the use of real-time PCR for predicting disease severity and death (2, 6, 12). Ho et al (6) found that the mecA DNA level among patients with methicillin-resistant S. aureus bacteremia was significantly higher in nonsurvivors than in survivors. Also, Iwaya et al (7) demonstrated in a mouse infection model that real-time PCR was useful for accurately estimating Serratia marcescens cell numbers in blood and for predicting the severity of septicemia.…”
mentioning
confidence: 99%